The genius of design by Chris Wilson; Denis Lawson; Anthony Burke; Wall to Wall Media.; Acorn Media (Firm); et al. - Wilson, Chris (Silver Spring, MD Distributed by Acorn Media, 2010)
Every aspect of modern life is influenced by industrial design, from office chairs to apartment complexes. This fascinating series delves into the personalities and technology that shape the world's environment, economy, and culture.
Narrator Denis Lawson.
Bonus features: biographical sketches, discussion questions, famous flops.
DVD
disc 1 (145 min.). ep. 1. Ghosts in the machine -- ep. 2. Designs for living -- ep. 3. Blueprints for war -- disc 2 (97 min.). ep. 4. Better living through chemistry -- ep. 5. Objects of desire.
Producers/directors, Chris Wilson, Peter Sweasey, Chris Rodley, Hattie Bowering ; narrator, Denis Lawson ; music, Anthony Burke ; series producer, Tim Kirby.
Keywords: Industrial design -- History; Industrial design; Design